The Impact of English on Products Branding in a Non-Speaking English Area: Customers’ Perception - Sri Gustiani; Moehamad Ridhwan; Yusri Yusri (State Islamic University of Raden Fatah Palembang, South Sumatra, Indonesia, 2022)
This study detailed the impacts of English on products branding from customers’ point of view. It was limited in food, electronics, and garment as the three most traded products in Palembang city as one of the five biggest trading cities in Indonesia. Using a qualitative method with individual and focus group interviews for data collecting techniques, there were 15 participants involved in individual interviews and 30 participants in a focus group interview. Due to physical restrictions during the Covid-19 pandemic era, the interviews were conducted online with semi-structured interview questions. The collected data were analysed using thematic analysis to unveil customers’ perception in the terms of popularity, purchasing interest, sales and revenue, business competition, curiosity, vocabulary, a symbol of modernity, and prestige toward products with English branding. It was revealed that the use of English on product branding highly impacted popularity, business competition, buyers’ curiosity, vocabulary, and the symbol of modernity of the users of the object products. Interestingly, electronics products were not affected by the use of English branding on purchasing interest, sales and revenue, and prestige, whereas food and garment products were. The English branding impacted the prestige of the customers only for garment products. Therefore, it is recommendable that certain products make use of English labelling for better recognition and acceptability in public.